Detection of miR-34a promoter methylation in combination with elevated expression of c-Met and β-catenin predicts distant metastasis of colon cancer - Siemens, Helge; Mansmann, Ulrich; Kirchner, Thomas; Hermeking, Heiko (Clinical cancer research, 2013)
Purpose: Here, we determined whether epigenetic inactivation of miR-34a and miR-34b/c genes may serve as a prognostic marker for distant metastases in colon cancer. Experimental Design: Using a case-control study design of 94 primary colon cancer samples with and without liver metastases, we determined CpG methylation frequencies of miR-34a and miR-34b/c promoters, expression of miR-34a, and its targets c-Met, Snail, and β-catenin and their prognostic value. Results: miR-34a methylation was detected in 45.1% (n = 42 of 93) of the samples and strongly associated with metastases to the liver (P = 0.003) and lymph nodes (P = 0.006). miR-34b/c methylation was detected in 91.9% of the samples (n = 79/86). A significant inverse correlation between miR-34a methylation and expression of mature miR-34a (P = 0.018) was detected. Decreased miR-34a expression was associated with upregulation of c-Met, Snail, and β-catenin protein levels (P = 0.031, 0.132, and 0.004), which were associated with distant metastases (P = 0.001, 0.017, and 0.005). In a confounder-adjusted multivariate regression model miR-34a methylation, high c-Met and β-catenin levels provided the most significant prognostic information about metastases to the liver (P = 0.014, 0.031, and 0.058) and matched pairs showed a higher prevalence of these risk factors in the samples with distant spread (P = 0.029). Finally, we obtained statistical evidence indicating that the simultaneous detection of these three markers has the highest prognostic value. Conclusions: Silencing of miR-34a and upregulation of c-Met, Snail, and β-catenin expression is associated with liver metastases of colon cancer. Detection of miR-34a silencing in resected primary colon cancer may be of prognostic value, especially in combination with detection of c-Met and β-catenin expression. Clin Cancer Res; 19(3); 710-20. ©2012 AACR.